Stopping nucleot(s)ide analogues in non‐cirrhotic HBeAg‐negative chronic hepatitis B patients: HBsAg loss at 96 weeks is associated with low baseline HBsAg levels. Issue 2 (6th May 2022) - Hall, Samuel A. L.; Burns, Gareth S.; Anagnostou, Despina; Vogrin, Sara; Sundararajan, Vijaya; Ratnam, Dilip; Levy, Miriam T.; Lubel, John S.; Nicoll, Amanda J.; Strasser, Simone I.; Sievert, William; Desmond, Paul V.; et al.
Summary: Background and Aims: Current guidelines recommend long‐term nucleot(s)ide analogue (NA) therapy for patients with HBeAg‐negative chronic hepatitis B (CHB). However, disease remission has been described after stopping NA therapy, as well as HBsAg loss. Methods: We performed a prospective multi‐centre cohort study of stopping NA therapy. Inclusion criteria were HBeAg‐negative CHB, the absence of cirrhosis and HBVDNA<lower limit of quantification for ≥18 months. We assessed virological and biochemical outcomes including HBsAg loss, as well as NA restart rates, over 96 weeks. Results: In total, 110 patients [62% entecavir (ETV); 28% tenofovir (TDF), 10% other] were enrolled. Median age was 56 years, 57% were male, 85% were Asian, median baseline HBsAg level was 705 (214–2325) IU/ml. Virological reactivation occurred in 109/110 patients, median time to detection was 8 (4–12) weeks, and occurred earlier after stopping TDF versus ETV (median 4 vs. 12 weeks p < 0.001). At week 96, 77 (70%) remained off‐treatment, 65 (59%) had ALT <2× ULN, 31 (28%) patients were in disease remission with HBVDNA <2000 IU/ml plus ALT <2× ULN and 7 (6%) patients had lost HBsAg. Baseline HBsAg ≤10 IU/ml was associated with HBsAg loss (6/9 vs. 1/101 p < 0.001). ALT >5× ULN occurred in 35 (32%); ALT flares were not associated with HBsAg loss. There were no unexpected safety issues. Conclusion: Virological reactivation was very common after stopping NA therapy and occurred earlier after stopping TDF versus ETV. The majority of patients had ALT <2× ULN at week 96, but only one‐third achieved disease remission and HBsAg loss was rare. Very low HBsAg levels at baseline were uncommon but predicted for HBsAg loss and disease remission. Abstract : Clinical outcomes over time—Intention to treat analysis of clinical outcomes in 110 patients who stopped NA therapy. Patients were classified into the following groups: HBsAg loss, Biochemical Remission (ALT <2× ULN), Virological Remission (HBV DNA <2000), or NA treatment restarted (Figure 1); Low baseline HBsAg levels were associated with higher likelihood of HBsAg loss and lower rates of Virological and Biochemical Relapse—(A) Baseline HBsAg level ≤10 IU/ml was associated with HBsAg loss – 6 of 7 patients who lost HBsAg had a baseline HBsAg level ≤10 IU/ml [HBsAg ≤10 IU/ml, HBsAg loss = 6/9 (67%) versus HBsAg >10 IU/ml, HBsAg loss = 1/101 (1%), p < 0.001, Figure 5]. Low baseline HBsAg levels were also associated with a lower rate of (B) virological relapse [HBsAg level ≤10 IU/ml, 3/9 vs. HBsAg level >10, 95/101, HR 0.15 (0.05, 0.47) p = 0.001] and (C) biochemical relapse [HBsAg level ≤10 IU/ml, 1/9 vs. HBsAg level >10, 54/101, HR 0.16 (0.02, 1.13) p = 0.066] through 96 weeks of follow‐up (Figure 2).